2017
DOI: 10.1093/jee/tox062
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Sogatella furcifera (Hemiptera: Delphacidae) Migratory Events on the Southern Rice Black-Streaked Dwarf Virus Epidemics

Abstract: Southern rice black-streaked dwarf virus (SRBSDV) caused serious rice losses. After the first outbreak in 2009 in northern Vietnam and southern China, the virus ravaged crops again on enormous scales in 2010, but infections have decreased sharply since 2011. We presumed that the sudden epidemics and fadeout of SRBSDV would be closely related to the migratory events of the insect vector, Sogatella furcifera. This study sought the source area of SRBSDV using the trajectory analysis method, and revealed the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…1) makes it ideally placed to receive large numbers of return migrants from southern China, and it lies to the south of the northern winter-breeding limit (around the Tropic of Cancer; Cheng, 1979;Luo et al, 2013). However, field surveys conducted as part of this study (Plates S1-S5) in NCV confirmed that there is a 3-month fallow period during November to January when no rice crops are grown, as previously reported (Wu et al, 2017), and rice at a suitable developmental stage for RPH colonization is not present until late-February at the earliest. As rice is the only food source of RPH, the absence of suitable hosts will disrupt the population cycle leading to an apparent gap in the migration loop.…”
Section: Introductionsupporting
confidence: 86%
See 3 more Smart Citations
“…1) makes it ideally placed to receive large numbers of return migrants from southern China, and it lies to the south of the northern winter-breeding limit (around the Tropic of Cancer; Cheng, 1979;Luo et al, 2013). However, field surveys conducted as part of this study (Plates S1-S5) in NCV confirmed that there is a 3-month fallow period during November to January when no rice crops are grown, as previously reported (Wu et al, 2017), and rice at a suitable developmental stage for RPH colonization is not present until late-February at the earliest. As rice is the only food source of RPH, the absence of suitable hosts will disrupt the population cycle leading to an apparent gap in the migration loop.…”
Section: Introductionsupporting
confidence: 86%
“…Thus the large populations which outbreak in southern and eastern China each summer (Hu et al, 2011(Hu et al, , 2018Lu et al, 2017) must return to Indochina during the autumn in order for the migratory populations to persist. Direct evidence for these southward return migrations was relatively scant until recently, and limited to a few observations of movements within China (Riley et al, 1991;Hu et al, 2013), but the current paper and recent work of Wu et al (2017) indicate that wind conditions suitable for transport from southern China to Indochina are frequent in the autumn. In particular, we identify the NCV region as a key area for the return migrants, with a high proportion of trajectories from the southern Chinese provinces of Guangdong, Guangxi, and especially Hainan, reaching NCV (Fig.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…S. furcifera can migrate over long distances in temperate and tropical regions of Asia and primarily feeds on rice plants ( Shen et al, 2005 ; Ma et al, 2017 ), from which it sucks sap, causing yellowing, stunting, and hopper burn, and finally plant death ( Wang et al, 2017 ). More importantly, S. furcifera can transmit dangerous rice viruses, further contributing to the damage of rice plants ( Zhou et al, 2013 ; He et al, 2016 ; Wu et al, 2017 ). Therefore, it is important to investigate the immune mechanisms of S. furcifera to develop effective control strategies.…”
Section: Introductionmentioning
confidence: 99%